Pendampingan Penulisan Karya Tulis Ilmiah dan Publikasi Bagi Guru RA di Kabupaten Temanggung - Hastuti, Asih Puji (Transformatif : Jurnal Pengabdian Masyarakat, 2024)
This mentoring activity aims to increase the knowledge and abilities of RA teachers in Temanggung Regency in writing scientific papers and publications, as well as improve their skills in writing scientific papers. The implementation of this community service uses the participatory learning and action (PLA) method, which is carried out offline. Participatory Learning and Action (PLA) is a learning method with participatory practice. The service participants were 17 Raudhatul Athfal teachers in Temanggung Regency. The results of the service show that there is an increase in teacher knowledge about how to write scientific journals and how to publish them. This can be seen in the results of the pretest and posttest of the activities given before and after they are carried out.